1998
DOI: 10.1002/hep.510280231
|View full text |Cite
|
Sign up to set email alerts
|

Transport of fluorescent bile acids by the isolated perfused rat liver: Kinetics, sequestration, and mobilization

Abstract: Hepatocyte transport of six fluorescent bile acids containing nitrobenzoxadiazolyl (NBD) or a fluorescein derivative on the side chain was compared with that of natural bile acids using the single-pass perfused rat liver. Compounds were infused at 40 nmol/g liver min for 15 minutes; hepatic uptake and biliary recovery were measured; fractional extraction, intrinsic basolateral clearance, and sequestration (nonrecovery after 45 minutes of additional perfusion) were calculated. Fluorescent bile acids were effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 53 publications
4
28
0
1
Order By: Relevance
“…Ntcp) and bile-salt secretory (i.e. Bsep) systems at the basolateral and canalicular surface domains, respectively (Holzinger et al, 1998;Holzinger et al, 1997). Hence, the data are fully consistent with the development of a functionally competent transport polarization in longterm-cultured small hepatocytes.…”
Section: Functional Transport Competence Of Differentiated Hepatic Orsupporting
confidence: 76%
See 1 more Smart Citation
“…Ntcp) and bile-salt secretory (i.e. Bsep) systems at the basolateral and canalicular surface domains, respectively (Holzinger et al, 1998;Holzinger et al, 1997). Hence, the data are fully consistent with the development of a functionally competent transport polarization in longterm-cultured small hepatocytes.…”
Section: Functional Transport Competence Of Differentiated Hepatic Orsupporting
confidence: 76%
“…2,2′-Azinobis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) was from Fluka (Buchs, Switzerland). The fluorescent bile salt cholylglycyl-fluorescein (Holzinger et al, 1998;Holzinger et al, 1997) was a gift from A. F. Hofmann (University of California, San Diego, CA). All other chemicals and reagents were of analytical grade and were readily available from commercial sources.…”
Section: Chemicalsmentioning
confidence: 99%
“…In this context, we recently reported on the characterization of the hepatic disposition of the bile salt analog cholyl-glycylamido-fluorescein (CGamF) in animal and human hepatocytes (Ye et al, 2008;Ye et al, 2009). CGamF was synthesized by conjugation of 5-aminofluorescein with the carboxylic group of the natural bile acid cholylglycine yielding a fluorescent bile salt analogue (Holzinger et al, 1998). The utility of CGamF as a convenient fluorescent probe simulating bile salt transport in various in vitro and in vivo models of different species has been demonstrated previously (Maglova et al, 1995;Bravo et al, 1998;Holzinger et al, 1998;Mita et al, 2006).…”
mentioning
confidence: 99%
“…CGamF was synthesized by conjugation of 5-aminofluorescein with the carboxylic group of the natural bile acid cholylglycine yielding a fluorescent bile salt analogue (Holzinger et al, 1998). The utility of CGamF as a convenient fluorescent probe simulating bile salt transport in various in vitro and in vivo models of different species has been demonstrated previously (Maglova et al, 1995;Bravo et al, 1998;Holzinger et al, 1998;Mita et al, 2006). Mita et al (2006) showed that CGamF as well as other fluorescent bile salt analogues were transported across LLC-PK1 cells co-expressing NTCP (SLC10A1) and BSEP (ABCB11), albeit at a substantially lower rate than the natural bile salt taurocholate.…”
mentioning
confidence: 99%
“…El compuesto final que se obtuvo está descrito y es conocido como colilamidofluoresceína (CamF). [72,[79][80] Brevemente, la ruta sintética descrita para su preparación se basó en la condensación de la 4-aminofluoresceína comercial con el ácido cólico utilizando Así pues, partiendo de ácido cólico se puede preparar una familia de intermedios versátiles que permitan la conjugación con otros fluoróforos.…”
Section: Aminofluoresceína (Amf)unclassified